2021
DOI: 10.1111/ejss.13167
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal accumulation in agricultural soils from mineral phosphate fertiliser applications in European long‐term field trials

Abstract: Mineral phosphate (P) fertilisers are the main suspected sources of uranium (U) and cadmium (Cd) input to agricultural soils. This study was set up to survey the general long‐term impact of P fertilisers on concentrations of Cd, U and other trace metals in European soils. A total of 218 soil samples was collected from 15 long‐term (3–78 years, median 18 years) P trials at 11 locations with a pairwise comparison of topsoil composition between the fertilised and corresponding unfertilised soils. Aqua regia soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The applications of P fertilizers have been reported to enhance U concentrations in agricultural soils on different continents around the world. For instance, in Asia [15][16][17][18][19][20][21][22][23][24][25][26], similar in Europe [16][17][18][19][20], in Australia [21,22], in America [23][24][25][26], and in Africa [27][28][29][30][31]. This study revealed that from all reviewed articles, the concentration of U from Minjingu P fertilizers from Tanzania ranged from 200 to 600 mg kg −1 , which is similar to what is found in open-pit commercial uranium mines in Namibia.…”
Section: Introduction 1background Informationsupporting
confidence: 73%
“…The applications of P fertilizers have been reported to enhance U concentrations in agricultural soils on different continents around the world. For instance, in Asia [15][16][17][18][19][20][21][22][23][24][25][26], similar in Europe [16][17][18][19][20], in Australia [21,22], in America [23][24][25][26], and in Africa [27][28][29][30][31]. This study revealed that from all reviewed articles, the concentration of U from Minjingu P fertilizers from Tanzania ranged from 200 to 600 mg kg −1 , which is similar to what is found in open-pit commercial uranium mines in Namibia.…”
Section: Introduction 1background Informationsupporting
confidence: 73%
“…The aqua regia U and Cd concentrations in this study are lower for U, not for Cd, than the real total soil concentrations (microwave digestion with HF, HNO 3 and H 2 O 2 ) measured by Bigalke et al (2020) (Table 1). This was expected as aqua regia does not dissolve silicates and thus omits the U bound in the silicate crystal lattice, which is unavailable for leaching processes and plant uptake (Bergen et al, 2021). The NE soil has limestone throughout the soil profile, which is relevant for U as soluble uranyl carbonate complexes can form (Langmuir, 1978).…”
Section: Soil Compositionmentioning
confidence: 99%
“…The assessment of the annual leaching of Cd in soil at an EU‐wide scale was the most critical part of the Cd regulation (Bergen et al, 2023; Verbeeck et al, 2020) and was open to criticism (Sterckeman et al, 2018), hence calling for more reliable data and models. In contrast to Cd, there is no EU legislation yet for uranium (U) in P fertilizers, even though soil U concentrations change more significantly and more markedly than soil Cd in response to long‐term P fertilization (Bergen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PRs are the primary source of trace elements (TEs) incorporated into mineral fertilizer, such as V, Cr, As, Se, Mo, Cd, and U. Accumulation of some of these elements has been observed in agricultural soils and can be highly variable based on fertilizer utilization and soil chemical properties. , Several studies have investigated the Sr isotope ratio ( 87 Sr/ 86 Sr) in PRs, and one study has shown the similarity between the 87 Sr/ 86 Sr ratio of PRs and mineral fertilizers originating from the same geographical region . Additionally, a few studies have characterized and applied the Sr isotope ratio of fertilizer as a tracer for delineating their environmental impact. ,− However, these studies have investigated the occurrence of TEs and the utility of Sr isotopes only in specific case studies.…”
Section: Introductionmentioning
confidence: 99%